Reading interests of grade 7-10 students of the University of the Philippines Integrated School - Balaba, Zenaida T. 1979-; Santos, Herminia H.
Nowadays, people are more hooked watching cable TV or surfing the Internet especially among the children and teenagers than reading a book or even a newspaper. The library must recognize the reading interests of its clientele to be able to promote and encourage them to read more books and appreciate learning through books. This study was an investigation of the reading interests of Grade 7-10 students of the University of the Philippines Integrated School (UPIS) enrolled in school year 2000-01.Sixty-nine (86.3 percent) out of 80 questionnaires retrieved were utilized in the study and majority of the respondents were female (44 or 63.8 percent); their parents obtained a college education (80 or 58.0 percent) and the family's annual income ranged from Php 100,001 and above (38 or 55.1 percent).The findings further showed the students have positive reading interests; they read books (60 or 87.0 percent), magazines (58 or 84.1 percent), comics (49 or 71.0 percent), newspapers (58 or 84.1 percent) except journals (68 or 98.6 percent). The three main reasons why they read books are: to fill in their free time (43 or 21.7 percent), give them information (33 or 16.7 percent), and improve their vocabulary (33 or 16.7 percent). On the other hand, the respondents' reading interests were influenced mainly by their personal initiatives, choices and preferences. The primary means of acquiring reading materials are by borrowing from friends, classmates, neighbors, etc. and by purchase. With regards to the relationship of grade, gender, family annual income and parents' educational attainment and reading interests, the chi-square test was used to determine the significance of the variables. It was found that only gender had a significant relationship; all the other variables had no significant relationship with reading interests.
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman.
Vita
Keywords: Books and reading -- Philippines -- Quezon City; Reading interests -- Philippines -- Quezon City; University of the Philippines Integrated School